PENGOLAHAN DAGING AYAM FROZEN SEBAGAI PENINGKATAN PEMASARAN AYAM POTONG - Tjipto Sajekti; Dedi Supiyadi; Arie Hendra Saputro (Universitas Mataram, 2022)
The problem that occurs is that there are many unsold chicken stocks and are sold at low prices. The solution to this problem is to provide product differentiation in the form of frozen food products with product innovations that have been cooked ready to serve with the addition of instant spices such as chili sauce and others. This Community Service (PKM) aims to assist, provide training and provide guidance to UKM Ayam Sapi.Com in increasing production and marketing capacity on a national scale. With mentoring and training for partners, it is hoped that the conditions for partners can survive and further develop their business businesses. The methods achieved to overcome the problems faced by AyamSapi.com as partners are as follows: 1) Processing of chicken meat with frozen food technology, 2) making simple financial reports. Business development requires product innovation as a new variant. Innovation helps partners survive and develop products. The results of the activities that can be generated from this service activity are partners can innovate in making frozen food products. The existence of product innovation will help partners to survive the crisis and the covid 19 pandemic. Frozen food is a form of product innovation to be able to provide added value and reduce rotting raw materials, so that raw chicken pieces are not wasted. The result of other activities is that partners can compile financial reports according to financial accounting standards, assist partners in tracking and directly monitoring the income and expenses that have been made by partners. With frozen food, it is one of the products that can increase the selling value of partners so that partners avoid losses.